Helicobacter pylori Infection Is Associated with Type 2 Diabetes, Not Type 1 Diabetes: An Updated Meta-Analysis - Jun-Zhen Li; Jie-Yao Li; Ting-Feng Wu; Ji-Hao Xu; Can-Ze Huang; Di Cheng; Qi-Kui Chen; Tao Yu (Gastroenterology Research and Practice)
Background. Extragastric manifestations of Helicobacter pylori (H. pylori) infection have been reported in many diseases. However, there are still controversies about whether H. pylori infection is associated with diabetes mellitus (DM). This study was aimed at answering the question. Methods. A systematic search of the literature from January 1996 to January 2016 was conducted in PubMed, Embase databases, Cochrane Library, Google Scholar, Wanfang Data, China national knowledge database, and SinoMed. Published studies reporting H. pylori infection in both DM and non-DM individuals were recruited. Results. 79 studies with 57,397 individuals were included in this meta-analysis. The prevalence of H. pylori infection in DM group (54.9%) was significantly higher than that (47.5%) in non-DM group (OR = 1.69, P<0.001). The difference was significant in comparison between type 2 DM group and non-DM group (OR = 2.05), but not in that between type 1 DM group and non-DM group (OR = 1.23, 95% CI: 0.77–1.96, P=0.38). Conclusion. Our meta-analysis suggested that there is significantly higher prevalence of H. pylori infection in DM patients as compared to non-DM individuals. And the difference is associated with type 2 DM but not type 1 DM.